2021
DOI: 10.1177/07067437211023103
|View full text |Cite
|
Sign up to set email alerts
|

The Ontario Forensic Mental Health System: A Population-based Review

Abstract: Objective: The purpose of this study was to increase the understanding of the Canadian forensic psychiatry system by providing a population-based overview of the Ontario forensic mental health system. Methods: Data were collected on 1,240 accused adults who were subject to the jurisdiction of the Ontario Review Board (ORB) between 2014 and 2015. Archival data were retrieved from annual ORB hearing hospital reports for accused supervised by all nine adult forensic psychiatry facilities across Ontario. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…This reflects that one of our data collection sites was a male-only facility, but is also consistent with the finding that the most serious forms of violence still tend to be dominated by men. Individuals in this sample otherwise showed rates of personality and substance use disorders, as well as rates of prior criminal justice involvement, comparable to those for the larger and more heterogeneous population of forensic service users in Canada [39][40][41] (see Supplementary Table 1, available at https://doi. org/10.1192/bjo.2023.567).…”
Section: Patient and Victim Typesmentioning
confidence: 66%
“…This reflects that one of our data collection sites was a male-only facility, but is also consistent with the finding that the most serious forms of violence still tend to be dominated by men. Individuals in this sample otherwise showed rates of personality and substance use disorders, as well as rates of prior criminal justice involvement, comparable to those for the larger and more heterogeneous population of forensic service users in Canada [39][40][41] (see Supplementary Table 1, available at https://doi. org/10.1192/bjo.2023.567).…”
Section: Patient and Victim Typesmentioning
confidence: 66%
“…The present study aims to fill this gap by examining the role of psychopathy in the link between ACEs and self-harming behaviours among forensic patients. The study utilized data from individuals under the Ontario Review Board Database (ORB) in 2014 and 2015 [ 23 ]. The database was created to capture information from ORB reports for a defined period on study-specific items, including measures of ACEs, psychopathy, and self-harm [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study utilized data from individuals under the Ontario Review Board Database (ORB) in 2014 and 2015 [ 23 ]. The database was created to capture information from ORB reports for a defined period on study-specific items, including measures of ACEs, psychopathy, and self-harm [ 23 , 24 ]. The study will test the hypothesis that psychopathy mediates the effect of ACEs on self-harm.…”
Section: Introductionmentioning
confidence: 99%
“…Deinstitutionalization and an overburdened health care system have contributed to the steadily increasing rates of mental illness in prisons and community corrections, Abracen et al (2014 , 2016) . Previously those individuals diagnosed with major mental illness (MMI) were thought to belong strictly to the forensic psychiatric realm, but research shows that in fact, many individuals who are found not criminally responsible or unfit to stand trial have previous criminal charges and convictions, with a significant proportion having served custodial sentences ( Moulden et al, 2014 ; Skeem et al, 2014 ; Moulden and Myers, 2017 ; Chaimowitz et al, 2021 ). The fluidity between systems suggests that some knowledge can be shared about individuals with mental illness, regardless of how their behavior is adjudicated.…”
Section: Introductionmentioning
confidence: 99%